The role of methionine cycle disruption in the initiation and progression of malignant tumors - T. G. Ruksha; M. N. Kurbat; N. V. Palkina; V. A. Kutsenko (Успехи молекулярной онкологии)
The methionine cycle is responsible for the metabolism of substances associated with methionine, one of the essential amino acids for protein synthesis. The methionine cycle dysregulation leads to non-proteinogenic amino acid homocysteine accumulation that can have a negative impact on a health. Numerous studies describe homocysteine effect on cardiovascular pathology development but its role in carcinogenesis remains poorly understood. Therefore, the purpose of this review is to analyze scientific data regarding the role of methionine catabolism dysregulation in a cell neoplastic transformation and tumor growth. Understanding cellular alterations of methionine metabolism is important for novel anti-cancer drugs development as well as establishing approaches for combinatorial treatment strategies aiming to overcome metabolic plasticity of cancer cells and their drug resistance.